Analisis Efektivitas Penagihan Tunggakan Pajak Dengan Surat Paksa Dalam Rangka Meningkatkan Penerimaan Pajak Di Kpp Pratama Jakarta Matraman Tahun 2019-2021 - Widya Lamriado; Budhi Yuwono (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to determine the implementation of import supervision of consignments in an effort to increase compliance of customs service users at the Supervision and Service Office of Type-C Intermediate Customs and Excise (KPPBC Type Madya Pabean C) in Kantor Pos Besar, Pasar Baru, in 2020. The phenomenon of this research is that the enactment of new regulations, which increase e-commerce transactions, can lead to illegal transactions, entry of prohibited goods, and restrictions as well as actions to break the value of consignments with the aim of avoiding import duty rates. This study uses a qualitative method with a qualitative descriptive approach. The results show that the implementation of import supervision of consignments at KPPBC Type Madya Pabean C, in Kantor Pos Besar, Pasar Baru, in 2020 greatly affected the compliance of users of imported goods services. In its implementation, there were several obstacles, such as a lack of understanding of customs service users, facilities and infrastructure that need to be improved and an unbalanced number of human resources. Therefore, it is necessary to make efforts to make campaign in the media and layers of society and to improve the facilities and infrastructure needed as well as the quality of human resources.